Heart rate during sleep in PTSD patients: Moderation by contact with a service dog - Woodward, Steven H.; Jamison, Andrea L.; Gala, Sasha; Lawlor, Catherine; Villasenor, Diana; Tamayo, Gisselle; Puckett, Melissa (Biological psychology, 2023)
There is growing interest in the potential health benefits of dog ownership in both the lay and scientific communities. Large reductions in risk for cardiovascular disease and all-cause mortality in dog owners relative to non-owners have been observed in epidemiological samples. Persons diagnosed with posttraumatic stress disorder exhibit elevated risk for cardiovascular disease. The current study tested a sample of 45 U.S. military veterans with deployment-related posttraumatic stress disorder employing an intensive, longitudinal, within-subjects design contrasting sleep heart rate on nights with and without a service dog. As participants were engaged in residential psychiatric treatment, sleep opportunities, waking activities, meals, and medications, were consistently scheduled. The primary recording methodology, mattress actigraphy, enabled passive quantification of heart rate over a total sample of 1097 nights. Service dog contact was associated with reduced sleep heart rate especially in participants with more severe PTSD. Longer-term longitudinal studies will be needed to assess the durability and asymptotic magnitude of this effect. An unexpected effect of nights in study was associated with increased heart rate consistent with hospitalization-associated deconditioning. •In Veterans in residential treatment for PTSD, contact with a service dog was associated with decreased sleep heart rate.•Over 29 nights of participation, sleep heart rate increased 2 BPM, compatible with hospital-associated deconditioning.•Selection bias is unlikely to fully explain associations between dog ownership and reduced cardiovascular disease.